Optimalisasi Promosi UMKM Sepinggan Baru Melalui Pemasangan Banner KKN - Luhfita Sari Ratna; Gabe Lorinsius Sinaga; Andhika Prasetya Wirawan; Mohammad Reyhan Fadh; Serafim Serafim; Ade Syahputra Pratama; Surya Atmaja; Putri Amalia; Ridha Caesarani Pradani; Difa Putri Auliya (Lembaga Pengembangan Kinerja Dosen, 2025)
Banners are a simple yet highly effective promotional strategy for MSMEs. With attractive designs and strategic placement, banners can increase business visibility and attract more customers, thus contributing to local economic growth. The installation of banners as a promotional strategy for Micro, Small, and Medium Enterprises (MSMEs) has been proven effective in increasing product visibility and sales. The discussion in this Community Service activity report describes the activities to promote MSMEs that take place in the Sepinggan Baru village. So, to support these activities, visual media is needed that can help optimize the promotion of MSMEs by installing banners. Banners are designed in various sizes that can be attached to MSMEs, so that villagers who have MSMEs can easily place the position of the banners to be installed. KKN students of Sepinggan Baru Village who are banner instructors and help install banners and RT.17 community members are very enthusiastic and grateful for the banners we provide, because it makes it easier for them to promote their businesses. The results of this activity show that the objectives of the activity were carried out well and the residents of RT.17 Village Sepinggan Baru who have MSMEs were very appreciative.